Factors affecting dental job satisfaction - A cross-sectional survey in Turkey - MUMCU, GONCA (SAGE PUBLICATIONS INC, 2004)
In this cross-sectional study, a randomly selected group of dentists (n = 855) from nine provinces of Turkey were interviewed for their levels of intrinsic, extrinsic, and overall job satisfaction. The proportion of overall job satisfaction was computed as the proportion of dentists who had mean general satisfaction scores greater than or equal to4 on a 5-point, Likert-type scale and was found to he 40.8% for the sample as a whole. The significant factors that affected overall satisfaction were age, the type of social insurance possessed, income level, the presence of dental auxiliaries, and the number of patients examined per day. Multivariate analysis of the data revealed that the type of social insurance, the amount of monthly income, and the number of patients examined per day were the most common and statistically significant predictors of intrinsic, extrinsic. and overall satisfaction in Turkish dentists.
Keywords: job satisfaction; Turkish dentists; socioeconomic factors; DENTISTS